Os valores humanos e o toque social afetivo: uma análise a partir de variáveis cognitivo-emocionais - Ribeiro, Maria Gabriela Costa (2021)
The current thesis aimed to verify the extent to which the relationship between human values and the affective social touch may be predicted by cognitive-affective variables. In Article 1, a systematic review was performed taking into account studies of social touch in the context of psychology between 2000 and 2020. The results indicated that this topic has become increasingly investigated in the last five years, encompassing research lines in the field of love relationships, the experience of social touch, the location of social touch, the psychological domain, and the relationship with an unknown person. Overall, these results showed the behavioral facet of this construct and its relationships with psychological well-being outcomes. Article 2 sought to elaborate and investigate the psychometric properties of the following measures: Affective Social Touch Scale (Recipient version; ASTC-R) and Affective Social Touch Scale (Provider version; ASTC-P). Three studies were performed and the first focused on the construction of the items (i.e., based-content validity). Specifically, 24 items were elaborated for both measures, ASTC-R and ASTC-P, and were submitted to judge evaluations: the results showed an agreement index above 0.83. The second study verified the dimensionality of these scales. Participants were 204 individuals (Mage = 28.8 years old; SD = 9.47), and they answered the initial versions of the ASTC-R and ASTC-P. A Principal Axis Factoring (Promax rotation) was performed for both scales. A parallel analysis, to determine the number of factors to be extracted, indicated a two-factor solution for ASTC-R presenting satisfactory reliability for both dimensions: touch receiver - intimate partner (α = 0.92) and touch receiver - family, friends, and strangers (α = 0.93). For the ASTC-P, under same procedures, a two-factor solution was observed, presenting satisfactory reliability for both dimensions: touch provider - intimate partner (α = 0.93) and provider touch – family, friends, and strangers (α = 0.94). Finally, the third study, aimed to confirm the factorial structure of the mentioned scales. Participants were 200 individuals (Mage = 29.7 years old; SD = 9.19), and they answered the same measures of the second study, with 43 items. The unifactorial, bifactorial and correlated multifactorial models were tested for both scales. Specifically, a four-factor model evidenced the best model-data fit for ASTC-R and ASTC-P (e.g., CFI = 0.99; TLI = 0.99; RMSEA = 0.03), in line with the Social Touch Theory. In sum, the studies provide evidence for the adequate psychometric parameters of both scales. Finally, Article 3 investigated the extent to which perceived social support and subjective well-being may predict the relationship between human values and affective social touch. In study 1 (n = 242; Mage = 29.0; SD = 10.75), of an exploratory nature, tested the relationship between human values, social touch and subjective well-being. In addition, the mediating role of subjective well-being was tested on the link: interactive values and affective social touch (receiver and provider) and its dimensions. In study 2 (n = 404; Mage = 29.3; SD = 9.33), it was observed that the inclusion of perceived social support as mediator, in addition to subjective well-being, explain the relationship between interactive values and affective social touch. In conclusion, the current results demonstrated the behavioral facet of the affective social touch, as well as expand the evidence for the correlates of this construct in Brazil toward indicators of psychological well-being and classical variables in the field of social psychology.